Persistent Effects of Historical Selective Logging on a Vascular Epiphyte Assemblage in the Forest Canopy of the Western Ghats, India - Seshadri, K. S.; Ganesan, R.; Devy, Soubadra M. (Frontiers in Forests and Global Change, 2021)
Forest canopies have been dubbed the last biological frontier and continue to remain underexplored. Vascular epiphytes form a rich assemblage of plants within the forest canopy and apart from sustaining diverse taxa, they also fulfill critical ecological functions. Vascular epiphytes are particularly sensitive to perturbations of microclimate and microhabitat within the canopy, especially from anthropogenic changes such as logging. The forests of the megadiverse Western Ghats in India harbor a rich assemblage of vascular epiphytes, but their ecology has not been examined systematically. We compared the diversity, abundance, and composition of a vascular epiphyte assemblage between an unlogged and a historically selectively logged forest in the southern Western Ghats, India, and identified factors affecting the epiphyte assemblage. Canopies of 100 trees each in selectively logged and unlogged forests were accessed using the single-rope technique. We found 20 species of vascular epiphytes with the assemblage dominated by members of Orchidaceae. The diversity and abundance of epiphytes were significantly greater in the selectively logged forest. One host tree, Cullenia exarillata, supported the greatest number of epiphytes in both forest stands. The niche widths of epiphyte species, computed with host tree species as a resource, were similar between the two stands but a greater number of species pairs overlapped in the selectively logged forest. Overall, epiphyte abundance was negatively associated with unlogged forests. Host tree species, tree height, and presence of moss on branches were positively associated with the abundance of epiphytes. Despite being ecologically important, no study has thus far examined the impact of selective logging on the epiphyte assemblage in the Western Ghats. Our findings contribute to the knowledge of vascular epiphytes from South and Southeast Asia and set the stage for future research and conservation.